The Influence of Industrial Work Practice (Internship), Corporate World Information, and Motivation of Entering Corporate World towards Working Readiness of Students at Class XII Office Administration Department in SMK Negeri 2 Temanggung 2018/2019 - Maria Sofa, Feni; Suryani, Nanik; Dyah Rahmawati, Fentya (KnE Social Sciences, 2020)
Vocational High School is an educational unit which aims to prepare graduates who are equipped with certain skills and expertise so that they are ready to enter the corporate world. The results of preliminary observations at SMK Negeri 2 Temanggung obtained data that the working readiness of students in office administration department was not optimal. The problem in this study is the number of absorptions of working graduates in the last 3 years showed that those who worked in office administration were less than 75% or less than the ideal number. The population in this study were all students of class XII Office Administration Department of SMK Negeri 2 Temanggung. Sampling technique used in this study was saturated sampling technique, with the number of respondents as many as 79 students. Data collection methods used, namely by observation, interview, documentation, and questionnaire. Data analysis used descriptive percentage analysis and multiple regression analysis by using SPSS for Windows version 24. The results of this study showed that there was simultaneous influence as much as 45.4%. Partially industrial work practice had influence as much as 17.64%, corporate world information had influence 5.34%, and motivation of entering corporate world had influence as much as 6.20% on working readiness. Keywords: Industrial Work Practice, corporate world information, motivation of entering corporate world, working readiness.